Management 2000: How to Maintain a Trouble-Free Workplace in the 1990s and Beyond - Gordon E. Jackson (Rocky Mountain Coal Mining Institute, 1991)
I read a book the other day called Opportunity 2000. The book, Opportunity 2000, talks about what's going to happen in the next nine or ten years as we propel ourselves through the 1990s into the 219 century. The book, Opportunity 2000, is a futuristic book, somewhat like Megatrends. It said that by the year 2000, baby boomers will be old people, and when you got here before the baby boomers, how does that make you feel? It said that there will be more women in the American work place by the year 2000 than men. The book, Opportunity 2000, discusses diversity. The big challenge for the 1990s is ?diversity?. We'll have the D-word in the 1990s. We had the G-word in the 1980s ? ?global.? Diversity in terms of more immigrants, more minorities, more females into the American work place, but also value systems diversity. We'll have to deal and adapt to four different generational clusters in dealing and interacting with employees and management in the 1990s-value systems diversity. I think there will be five generational clusters that we'll have to deal with. Massey says four. He says we'll still have the old people around, the World War II mentality; those who